Analysis of the Implementation of Resident Check-in Program in Mulyorejo Subdistrict, Surabaya City - Sophie Alifia Aphrodit; Amirul Mustofa (Journal of Politica Governo, 2024)
This research aims to determine the output of the Resident Check-In application in Mulyorejo Subdistrict, as well as the involvement and availability of human resources in its implementation. This study uses a qualitative method with data collection based on interviews, observations, and descriptive documentation. The results of the research indicate that the output achieved has not yet met the established targets. There are still issues faced, so the Resident Check-In application has not yet become a solution for problem-solving in Mulyorejo Subdistrict. Through community participation, the implementation of the Resident Check-In program is running well, and the feedback received is very positive. To address the shortfall in the output achieved, Mulyorejo Subdistrict is improving communication by utilizing current technology such as WhatsApp. Recommendations from this study include enhancing the implementation of the Resident Check-In application in Mulyorejo Subdistrict regarding the quality of the subdistrict officials' performance so that it can eventually become a good example for other subdistricts in producing outputs and increasing community participation. Additionally, further socialization regarding the Resident Check-In application is necessary so that residents will be more conducive to updating data. The results of this study can serve as a guide for the government to improve the existing system of the Resident Check-In application, to enhance the quality and efficiency of the performance of subdistrict officials in each area of Surabaya City. Moreover, it includes improving the quality of performance by developing officials in Mulyorejo Subdistrict.